Peran Kelompok Tani dalam Pengendalian Hama Penyakit Terpadu (PHT) Usahatani Padi di Kecamatan Makale - Tampang, Bertha; Yunus, Awaluddin; Ibrahim, Helda (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The issue of global food security is increasingly pressing amidst climate change, population growth, and environmental degradation. The agricultural sector, particularly rice production, faces threats from pests and diseases that reduce crop yields and farmer incomes. Climate change exacerbates pest attack patterns, increasing crop losses. In addition, excessive use of chemical pesticides leads to pest resistance and negative impacts on ecosystems and human health. This study used a descriptive method with a qualitative approach, and the study population included farmers who cultivate rice fields and farmer groups that have received Integrated Pest Management (IPM) in Makale District, Tana Toraja Regency, with a population of 325 families. Respondents were randomly selected at 15% of the total population, with a sample of 49 farmers consisting of three farmer groups. The results showed that the role of farmer groups in IPM implementation in Makale District includes extension and training (65.5%), facilitating access to information and resources (69%), decision-making (67.5%), and conflict management and IPM cooperation (66.5%). Therefore, it is necessary to strengthen the implementation of the rice farming system, with support from the Government and the Tana Toraja Regency Agriculture Service to optimize the development of rice farming businesses.